Dabigatran Reversal With Idarucizumab and In-Hospital Mortality in Intracranial Hemorrhage: A Systematic Review of Real-Life Data From Case Reports and Case Series - Frol, Senta; Sagris, Dimitrios; Šabovič, Mišo; Ntaios, George; Oblak, Janja Pretnar (Frontiers in Neurology, 2021)
Background: Intracranial hemorrhage (ICH) is a severe and possibly fatal consequence of anticoagulation therapy. Idarucizumab is used in dabigatran-treated patients suffering ICH to reverse the anticoagulant effect of dabigatran. Systematic review of real-life mortality in these patients is missing. Objectives: A review of all published dabigatran-related ICH cases treated with idarucizumab was performed. We aimed to estimate in-hospital mortality rate in these patients. Methods: We searched PubMed and Scopus for all published cases of ICH in idarucizumab/dabigatran treated patients until 15/5/2021. The assessed outcome was in-hospital mortality. Results: We identified 6 eligible studies (case series) with 386 patients and 54 single case reports. In-hospital mortality rate was 11.4% in case series, and 9.7% in case reports. Conclusions: Our analysis provides clinically relevant quantitative data regarding in-hospital mortality in idarucizumab/dabigatran treated patients with ICH, which is estimated to be 9.7-11.4%.